(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The primary purpose of teacher evaluation is personal and professional growth that leads to improved performance. The principalacts as a facilitator for each teacher, just as the teacher serves as a facilitator for students in the classroom. Teacher evaluation is an important tool to improve teaching learning achievement. If teacher teach lecture method of one subject and the another subject teacher teach to their students other psychological methods as like demonstration, project and problem solving methods. After evaluation we find that those students whose teachers teach them to psychological methods, they have more achievement in comparison to lecture method. More than two decades of research findings are unequivocal about the connection between teacher quality and student learning. Indeed, What Matters Most: Teaching for America’s Future (1996), the influential report of the National Commission on Teaching and America’s Future, made teaching the core of its “three simple premises” in its blueprint for reforming the nation’s schools. They are:What teachers know and can do is the most important influence on what students learn.